The World Vision International Child Empowerment Program in Yahim Village: Implementation, Impacts and Challenges - Nait, Shandy Angelica; Setiawan, Aria Aditya; Farneubun, Petrus K. (Papua Journal of Diplomacy and International Relations, 2023)
Indonesia guarantees the right of every child to enjoy protection from the state, including protection from sexual and economic exploitation that threatens their lives. This study attempts to assess the implementation, the impacts, and the challenges of the WVI child empowerment program from the time it was first introduced in Yahim village in 2018 to the year 2021. A qualitative method is used in this study in conjunction with a descriptive approach to explain the topic. Primary sources, such as interviews, field notes, personal documents, and other official documents, as well as secondary sources, such as books, journals, and media articles, are also used in this study. This article shows that WVI implemented the programs successfully, despite facing some external challenges. The program has had some impacts, including a decrease in cases of violence against children, an increase in children’s interest in literacy and gender equality, and children’s activeness in expressing their voices about their rights. A key conclusion is that providing children with access to empowerment programs should be sustained as it will result in better long-term outcomes. Hence, WVI and other humanitarian organizations need to expand similar programs to other villages/ communities. KEYWORDS Children’s rights; Empowerment; WVI; Yahim